Sterilization Effectiveness Of Rubber Leaf Explant (Hevea brasiliensis) In In-Vitro Culture - Lukmana, Mila; Rahmawati, Linda (BIOPROSPEK: Jurnal Ilmiah Biologi, 2018)
Rubber (Hevea brassiliensis), are the commodities that have the potential to be developed. Rubber cultivation is currently only rely on rootstocks obtained from seeds in the nursery, so availability is limited by seasons and seed viability. Tissue culture techniques to address challenges to obtain seeds in large quantities in a short time. Tissue culture are often faced with the problem of contamination, so that the required ingredients for the success of the sterilizing effective planting rubber leaf explants in vitro. Variables observed among other things, the speed of contamination of explants, number of explants of living, the number of types of contaminants, the number of sources of contaminants as well as the number of explants browning and not because browning. Sterilization treatment in this study, namely P1 without sterilization in LAFC, P2 with 70% alcohol, P3 combination treatment NaOCl 20% and 70% alcohol, P4 uses a combination of HgCl2 a 0.01% and NaOCl 10% and P5 using 70% alcohol and H2O2 17.6 % (v/v). The results showed that the treatment P1 bacterial contamination of 60% and mushrooms 85%, P2 bacterial contamination by 90% and mushrooms 10%, P3 bacterial contamination 92.5% and mildew 17.5%, P4 bacterial contamination 72.5% and fungi 10% and the treatment P5 with 65% of bacterial contamination without contamination of mushrooms. Best results are obtained by using the P5 treatment Alcohol 70% for 1 minute and H2O2 17.6% (v / v) for 20 minutes can remove contaminants fungi and suppress bacterial contamination percentage of 65% to 30 days after planting.